“Domesticating ‘Fallen Women’: Gender Violence and Detection in Lee Jackson’s A Metropolitan Murder (2004)” - Romero-Ruiz, María Isabel (My University, 2022)
Poverty and prostitution were some of the most important concerns for the Victorian mind and lots of associations and charities were established by the middle-class who tried to put an end to what was known as the “Great Social Evil”. At the same time, violence against women was another issue that provoked social uproar, especially when murder in strange circumstances happened. Many of the victims of this gender and sexual violence were fallen women marked by the stigma of their lack of respectability. Their bodies were disposable bodies and their lives were considered wasted lives not deserving the human condition. The Metropolitan Murder (2004) is part of Lee Jackson’s neo-Victorian trilogy whose protagonist Inspector Decimus Webb has as his aim to solve mysteries associated with the dark side of Victorian London. Also, he tries to restore order in the metropolis and clean it of the contamination and pollution that poverty and depravity convey. These characteristics find their echo in our current societies in the wasted lives of individuals who belong to the category of the “outcasts”. The aim of this paper is to analyse the lives of women in the Victorian past who carried the stigma of poverty and prostitution and were victims of all kinds of violence and discrimination. This analysis will be done under the prism ot theories associated with the notion of “watsed lives” and under the umbrella of the detection genre in neo-Victorian fiction.
Keywords: Jackson, Lee - Crítica e interpretación - Congresos; Novela histórica - Congresos; Mujeres - Malos tratos - En la literatura - Congresos; Prostitución - En la literatura - Congresos; Fallen women; Detective fiction; Neo-Victorian; Historical fiction; Gender violence